Hubungan antara Pengetahuan Gizi dan Uang Saku dengan Sikap dalam Memilih Makanan oleh Siswa SMA Islam PB Soedirman Selama Masa Pandemi Covid-19 - Syahla Alvira Rahma; Noerfitri Noerfitri (FORIKES, 2022)
During this pandemic, it is important for students to maintain a balanced nutritional diet based on knowledge and attitudes about nutrition to improve a good immune system so that it can be protected from the transmission of Covid-19. This study aims to find out the relationship of nutrition knowledge and pocket money to attitudes in choosing the food of Pb Soedirman Islamic High School students during the Covid-19 pandemic. Research design was observational research with cross-sectional design. The subject of the study was a grade X student of SMA Islam PB Sudirman who is still active and uses consecutive sampling method. The data was collected using a google form questionnaire analyzed using chi-Square statistical tests. The results of the analysis showed p-value of nutritional knowledge with nutritional attitude was 0.046 with OR 2.903 (95% CI = 0.987 – 8.537) and p-value of pocket money with nutritional attitude was 0.014 with OR 2.884 (95% CI = 1.224-6.796). The conclusion of this study was there is relationship between nutritional knowledge and pocket money with attitudes in choosing the food of PB Soedirman Islamic High School students during the Covid-19 pandemic. Keywords: nutrition knowledge; attitude in choosing foods; pocket moneyABSTRAKPada masa pandemi ini, penting bagi siswa untuk menjaga pola makan gizi seimbang yang didasari oleh pengetahuan dan sikap tentang gizi untuk meningkatkan sistem kekebalan tubuh yang baik sehingga dapat terlindung dari penularan Covid-19. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan gizi dan uang saku terhadap sikap dalam memilih makanan siswa SMA Islam PB Soedirman selama masa pandemi Covid-19. Desain penelitian merupakan penelitian observasional dengan rancangan cross-sectional. Subyek penelitian adalah siswa kelas X SMA Islam PB Soedirman yang masih aktif dan menggunakan metode consecutive sampling. Data dikumpulkan dengan menggunakan kuesioner google form dianalisis menggunakan uji statistik chi-Square. Hasil analisis menunjukkan p-value variabel pengetahuan gizi dengan sikap gizi yaitu 0,046 dengan OR 2,903 (95% CI = 0,987 – 8,537) dan p-value variabel uang saku dengan sikap gizi yaitu 0,014 dengan OR 2,884 (95% CI = 1,224-6,796). Kesimpulan dari penelitian ini terdapat hubungan antara pengetahuan gizi dan uang saku dengan sikap dalam memilih makanan siswa SMA Islam PB Soedirman selama masa pandemi Covid-19.Kata kunci: pengetahuan gizi; sikap dalam memilih makanan; uang saku